Bridging Gaps: How Authentic Leadership Transforms Compensation into Performance - Novitasari Dwi; Sisiawan Putra Riyan; Slamet Prasetyo Agung; Ika Desmadhani Salma; Sabaya Syavira (SHS Web of Conferences)
This study examines the role of authentic leadership as a mediator in the relationship between compensation, job satisfaction, and employee performance. The study was conducted at PT Serelia Prima Nutrisia, Yogyakarta, a company operating in the cereal industry utilizing local raw materials. The research employed a quantitative method with a cross-sectional design, using convenience sampling techniques, and data analysis was performed using the Structural Equation Model (SEM) method. The results indicate that authentic leadership fully mediates the relationship between compensation and job satisfaction with employee performance. Additionally, it was found that compensation and job satisfaction have a direct negative impact on performance. These findings contribute theoretically to the field of human resource management, particularly in understanding the factors that influence employee performance through the mediation of authentic leadership. The practical implications of this study highlight the importance of companies implementing authentic leadership to enhance employee performance.